Measuring Monetary Poverty in the Middle East and North Africa (MENA) Region: Data Gaps and Different Options to Address Them - Aziz Atamanov; Sharad Tandon; Gladys Lopez-Acevedo; Mexico Alberto Vergara Bahena (Institute of Labor Economics (IZA), 2020)
This paper identifies gaps in availability, access, and quality of household budget surveys in the Middle East and North Africa region used to measure monetary poverty and evaluates ways to fill these information gaps. Despite improving public access to household budget surveys, the availability and timeliness of welfare data in the Middle East and North Africa region is poor compared to the rest of the world. Closing the data gap requires collection of more HBS data in more countries and improving access to data where it exists. However, when collection of consumption data is not possible, a variety of other second-best strategies can be employed. Using imputation methods can help to measure monetary poverty. Constructing non-monetary poverty and asset indexes from less robust surveys, using non-traditional surveys such as phone surveys, and "big data"â exteuro"administrative records, social networks and communications data, and geospatial dataâ exteuro"can help substitute for, or complement data from existing traditional survey data.
Keywords: C81; I32; O10; 330; Middle East and North Africa; poverty; household budget surveys